Repeatability and agreement of two swept-source optical coherence tomographers and scheimpflug imaging for measurements of corneal curvature - Cheng, Shiming; Zhang, Jiasheng; Zhou, Kaijing; Li, Tiantian; Lin, Junhai; Yu, A.-Yong (BMC ophthalmology, 2024)
Purpose To evaluate the repeatability and agreement of two swept-source optical coherence tomographers and Scheimpflug imaging for corneal curvature in healthy subjects to obtain data on the clinical application of a new device. Methods This prospective study was conducted in January and February 2021 with 100 healthy subjects at the Eye Hospital of Wenzhou Medical University. Simulated keratometry (Sim-K), posterior keratometry (Kp), total corneal power (TCP), and total corneal astigmatism (TCA) were measured with CASIA2, Anterion, and Pentacam. Within-subject standard deviation (Sw), repeatability coefficient (RC), coefficient of variation (CoV), and intraclass correlation coefficient (ICC) were used to assess inter-device repeatability. Bland–Altman analysis was performed to determine inter-device agreement. Results The three devices showed good repeatability for Sim-K, Kp, and TCP with all ICC > 0.980. Pentacam showed the highest repeatability (ICC ≥ 0.993; ICC ≥ 0.993) while the CASIA2 demonstrated the lowest repeatability (ICC: ≥ 0.986; ICC: ≥ 0.985) for Sim-K and TCP. Anterion and CASIA2 revealed better repeatability (ICC ≥ 0.998; ICC ≥ 0.981) for Kp than Pentacam (ICC ≥ 0.980). Pentacam and Anterion showed good repeatability for TCA (ICC: 0.935 and 0.916), whereas the CASIA2 showed moderate repeatability (ICC: 0.836). Three instruments demonstrated good agreement with the maximum absolute 95% Limits of agreement (LoA) of 1.00 D for Sim-K, Kp, and TCP. Wide LoA were found for TCA with the maximum absolute 95% LoA ≥ 0.66 D between the three devices. Conclusions In healthy subjects, the three devices (Pentacam, Anterion and CASIA2) displayed comparable repeatability and accuracy for SimK, Kp, and TCP, and could be used interchangeably for these parameters. However, TCA measured by the three devices was not interchangeable. Trial registration Chinese Clinical Trial Registry Center (10/10/2020, ChiCTR2000038959).